Morphometric alterations, steatosis, fibrosis and active caspase‐3 detection in carbamate bendiocarb treated rabbit liver. Issue 2 (9th July 2013) - Petrovova, Eva; Purzyc, Halina; Mazensky, David; Luptakova, Lenka; Torma, Norbert; Sopoliga, Igor; Sedmera, David
ABSTRACT Increasing use of pesticides all over the world makes it necessary to reveal the toxic risk in populations of nontargeted organisms. Bendiocarb is one of the 12 insecticides recommended by the World Health Organization for use in malaria control in Africa, and is used against a variety of insects. The liver has an important role in its process of detoxication and excretion. In our experiment 56 adult rabbits of breed HY+, 28 males and 28 females were used. Animals were divided into groups (control, days 10, 20, 30 of bendiocarb administration). The presence of many binucleated hepatocytes, the highest number of liver cells and their decreased size at 10 day after bendiocarb administration was observed as an evidence of the hepatic regeneration. After the long‐term treatment pronounced changes were presented such as vacuolization and dilatation of hepatocytes, dilatation of sinusoids between hepatocytes, and focal infiltration of inflammatory cells. Numerous cells with caspase‐3 activity were present throughout the organ, most commonly around the portal tract and close to the central vein. Short and long‐term bendiocarb treatment showed the central vein thickened rim with increased deposition of collagen, spreading of collagen fibers into the perisinusoidal, and pericellular space surrounding the central veins, and septal fibrosis extended from the portal tract. Subsequently, presence of the lipid vacuoles both in the liver parenchyma and inner of the hepatocytes were observed. These results suggest that bendiocarb treatment leads to increased cell death, liver perisinusoidal fibrosis, and steatosis, especially during the long‐term administration. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 212–222, 2015.